Decreased Analgesic Requirements in Super Morbidly Versus Morbidly Obese Patients Undergoing Laparoscopic Sleeve Gastrectomy - Hamed Elgendy (14148846) (2020)
Background Scarce data exists about analgesic requirements in super morbidly obese (SMO) patients who underwent sleeve gastrectomy. We attempted to investigate analgesic requirements for SMO, when compared with morbidly obese (MO) individuals who underwent sleeve gastrectomy and its impact on postoperative outcome. Methods We studied 279 consecutive patients (183 MO, 96 SMO) who underwent bariatric surgery. Data analysis included perioperative anaesthetic management, analgesic consumptions, opioids side effects, and ICU admission. Results The SMO group showed higher patients with asthma, epilepsy, obstructive sleep apnoea (OSA), and ASA III percentages (P = 0.014, P = 0.016, P ˂ 0.001, and P ˂ 0.001, respectively). There were no significant differences in the total morphine consumption intraoperatively, or after 24 h. However, reduced consumption of intraoperative fentanyl and morphine in SMO when calculated per total body weight (TBW) (P = 0.004 and P = 0.001, respectively). At PACU, tramadol consumption per TBW and lean body mass (LBM) were significantly reduced in SMO (P = 0.001 and P = 0.025, respectively). Paracetamol consumption was significantly reduced in the SMO group (P = 0.04). They showed higher comorbidities (P ˂ 0.001), longer anaesthesia time (P = 0.033), and greater ICU admissions (P ˂ 0.001). Vomiting was higher in the MO group (P = 0.004). Both groups showed comparable pain scores (P = 0.558) and PACU stay time (P = 0.060). Conclusions Super morbidly obese patients required fewer opioids and analgesics perioperatively. They exhibited higher comorbidities with greater anaesthesia time and ICU admissions. PACU stay time and pain scores were comparable. Other Information Published in: Obesity Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11695-020-04559-4